189k views
0 votes
-2(2x-6)=8-(-5+3x)
how do you solve this ?

User Alfred Luu
by
4.4k points

1 Answer

4 votes

Answer:

x = -1

Explanation:

first you "remove the parentheses" by multiplying the number on the outside of them to everything on the inside. for instance, -2 x 2x = -4x and -2 x -6 = 12 (because whenever you multiply two negatives, it turns into a positive) then, when there is a minus sign in front of parentheses, you change the sign of everything within the parenthesis leaving you with a positive 5 and a negative 3x. so now you have a much simpler equation of -4x + 12 = 8 +5 -3x

next you want to of course add the 5 and the 8 to make it even more simple which would leave you with the equation:

-4x + 12 = 13 - 3x

The next thing you need to do is get the unknown variable on one side of the equation. So you do add 4x do get the x on the right side which would leave you with 12 = 13 - 3x + 4x

So now you can do the same thing to the 13 to try to get it on the left by subtracting 13 from both sides

12 - 13 = -3x + 4x

now you make the equation simple by "combining the like terms" (which is something you'll hear a lot in algebra class)

making you equation -1 = 1x

or just -1 = x because when you multiply something by 1, it's the same.


User Dvd
by
4.8k points